2004
DOI: 10.4049/jimmunol.172.6.3573
|View full text |Cite
|
Sign up to set email alerts
|

A Keratinocyte-Responsive γδ TCR Is Necessary for Dendritic Epidermal T Cell Activation by Damaged Keratinocytes and Maintenance in the Epidermis

Abstract: A unique population of T lymphocytes, designated dendritic epidermal T cells (DETC), homes to the murine epidermis during fetal development. DETC express a canonical γδ TCR, Vγ3/Vδ1, which recognizes Ag expressed on damaged, stressed, or transformed keratinocytes. Recently, DETC were shown to play a key role in the complex process of wound repair. To examine the role of the DETC TCR in DETC localization to the epidermis, maintenance in the skin, and activation in vivo, we analyzed DETC in the TCRδ−/− mouse. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
144
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(163 citation statements)
references
References 32 publications
17
144
2
Order By: Relevance
“…Importantly, the use of Tcrd-H2BEGFP mice provided here for the first time a direct proof that the ''depleted'' gd T cells were actually still present. This is a particular pity, since gd T-cell depletion avoids the limitations of the Tcrd knock-out model in which opportunistic ab T cells can occupy gd T-cell niches and may partially substitute the functions of genuine gd T cells [9]. Nevertheless, many recent studies found interesting effects after administration of anti-gd TCR mAb, mainly using the UC7-13D5 hybridoma [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the use of Tcrd-H2BEGFP mice provided here for the first time a direct proof that the ''depleted'' gd T cells were actually still present. This is a particular pity, since gd T-cell depletion avoids the limitations of the Tcrd knock-out model in which opportunistic ab T cells can occupy gd T-cell niches and may partially substitute the functions of genuine gd T cells [9]. Nevertheless, many recent studies found interesting effects after administration of anti-gd TCR mAb, mainly using the UC7-13D5 hybridoma [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the progress made in understanding their counterparts of the ab T-cell lineage, the biological role of gd T cells is only slowly emerging. Research on gd T cells must cope with various obstacles: (i) currently, information on gd TCR ligands is still very limited; (ii) in the mouse model and in the human system there is no other gd T-cell specific marker than the gd TCR itself; and (iii) the functional phenotype of TCR delta locus (Tcrd)-deficient (Tcrd -/-) mice [8] may be concealed by opportunistic ab T cells that occupy the niches of genuine gd T cells and might partially take over their functions [9]. However, a popular approach to overcome the latter issue is to deplete gd T cells in WT mice with mAb directed against gd TCR instead of using the Tcrd -/-model.…”
mentioning
confidence: 99%
“…19,25,26 In the murine system, distinct subsets of cd T cells bearing specific pairs of the c and d TCR chains are targeted to particular epithelial locations during development such as the skin, lungs, uterus, vagina and tongue where they make up a significant portion of the local intraepithelial lymphocyte population and appear to respond to endogenous stress-induced antigens that have yet to be unambiguously identified. [27][28][29][30][31] For some of these special niche localized cd T…”
Section: Species Specificity: the Best Laid Plans Of Mice And Men Oftmentioning
confidence: 99%
“…Skin cd T cells were found to be critical in wound healing, [58][59][60][61][62] and IL-17 was reported to be elevated in patients with inflammatory skin diseases. 63 However, the role of IL-17 in cutaneous wound healing, and whether it is produced by skin cd T cells, are less clear.…”
Section: Function In Tissue Repair and Inflammationmentioning
confidence: 99%